Produção de etanol a partir de sorgo sacarino com tratamento enzimático - Ferreira, Osania Emerenciano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The cultivation of sweet sorghum has agroindustrial features that makes it an economically promising raw material for the production of bioethanol. It stands out for short production cycle, low implementation cost, seed propagation, fully mechanized process, besides present a high energetic efficiency. This research aimed evaluate three sugar sorghum genotypes juice characteristics, harvested in two different seasons with and without the panicles and also evaluate the application of amylolytic enzymes under the ethanol production. The experiment was carried out through on 2013/2014 season, at 21° 14' 05 S and 48° 17' 09' W. The experimental design was completely randomized with split-split plots and four replications. The primary treatments were the sweet sorghum genotypes (CV147, CV198, and BRS508), the secondary treatments were the, the type of harvest (whole and stalks); the tertiary treatments were two sampling epochs (102 and 116 days after sowing - d.a.s.). To the clarification and must preparation steps we also used the quaternary treatment (with and without the application of enzymes). The sweet sorghum juice was subjected to the lime clarification and then treated with alpha-amylase and amyloglucosidase amylolytic enzymes, resulting in the must. Maser the yeast PE-2 was inoculated to initialize the fermentation process. He wine was recovered and characterized, calculating the fermentation efficiency and amount of ethanol (liters) per ton of sorghum. The processing of whole stalks reduced the ethanol production. The harvest seasons affect the technological quality of the juice, reflecting on the fermentation process. The use of amylolytic enzymes allowed us to obtain wines with lower levels of TRS and Brix, without affect the fermentative efficiency. The BRS508 genotype showed the highest production of ethanol (L/t) compared to CV147 and CV198

A cultura de sorgo sacarino apresenta características agroindustriais que torna a matéria-prima economicamente promissora para a produção de bioetanol. Destaca-se por ciclo produtivo curto, baixo custo de implantação, propagação por sementes, processo totalmente mecanizado, além de apresentar elevada eficiência energética. Esta pesquisa objetivou avaliar as características do caldo de três genótipos de sorgo sacarino, colhidos em duas épocas, com a sem panículas e a influencia da aplicação de enzimas amilolíticas sobre a produção de etanol. O experimento foi realizado na safra 2013/2014, localizada a 21°14'05'S e 48°17'09'W.O delineamento experimental foi o inteiramente casualizado, com parcelas sub-subdividas e quatro repetições. Os tratamentos primários foram os genótipos de sorgo sacarino (CV147, CV198 e BRS508), os secundários, o tipo de colheita (colmos integrais e colmos com remoção de folhas/panículas); os terciários as duas épocas de amostragem (102 e 116 dias após a semeadura- d.a.s.). Para a etapa de clarificação e preparo do mosto utilizou-se também o tratamento quartenário (com e sem aplicação de enzimas). O caldo de sorgo sacarino foi submetido a tratamento químico por calagem simples e posterior tratamento com enzimas amilolíticas alfa-amilase e amiloglucosidase, resultando no mosto. A seguir inoculou-se levedura PE-2 iniciando-se o processo fermentativo. Ao final o vinho foi recuperado e caracterizado sendo calculadas a eficiência fermentativa e produtividade de etanol (L.Mg-1). O processamento de colmos integrais reduziu a produção de etanol, as épocas de colheita afetam a qualidade tecnológica do caldo aumentando os teores de fenol, refletindo sobre o processo fermentativo. A utilização de enzimas amilolíticas possibilitou a obtenção de vinhos com menores teores de ARRT e Brix, sem afetar a eficiência fermentativa. O genótipo BRS508 foi o que apresentou...
Keywords: Biocombustíveis; Amido; Enzimas; Etanol; Sorgo sacarino; Biomass energy